2020
DOI: 10.7759/cureus.9729
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Insertion Trainer for Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA)

Abstract: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an emergency procedure designed to treat non-compressible torso hemorrhage. Because this is a high-acuity lowoccurrence event, it is difficult to train providers on the procedure and difficult for trained providers to stay proficient. Our primary objective was to develop a low-cost, high-fidelity teaching model to increase emergency medicine (EM) resident knowledge, confidence, and proficiency in performing REBOA. We utilized readily availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…99 Low-cost REBOA trainers have been developed, which could improve access to training resources in the austere setting. 100 Deterioration of skills may be seen with lack of exposure, however, and repeat training may be needed at 6-month intervals. 101 Resuscitative endovascular balloon occlusion of the aorta has been added as a skill included in the new Advanced Surgical Skills for Exposure in Trauma beta course, designed to train military members in essential trauma skills before deployment.…”
Section: Provider Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…99 Low-cost REBOA trainers have been developed, which could improve access to training resources in the austere setting. 100 Deterioration of skills may be seen with lack of exposure, however, and repeat training may be needed at 6-month intervals. 101 Resuscitative endovascular balloon occlusion of the aorta has been added as a skill included in the new Advanced Surgical Skills for Exposure in Trauma beta course, designed to train military members in essential trauma skills before deployment.…”
Section: Provider Trainingmentioning
confidence: 99%
“…Even more far forward, efforts have been made to train nonphysicians, including military medical technicians and nurses who may have earlier access to combat casualties and have been successful 99 . Low-cost REBOA trainers have been developed, which could improve access to training resources in the austere setting 100 . Deterioration of skills may be seen with lack of exposure, however, and repeat training may be needed at 6-month intervals 101 .…”
Section: Provider Trainingmentioning
confidence: 99%
“…Multiple studies including case reports and larger systematic reviews have demonstrated that the use of REBOA is associated with reduced hemorrhage and reduced blood product transfusions, particularly in the setting of invasive placental disorders such as placenta accreta [1,[3][4][5][6][7]. Multiple simulation studies have been published in both obstetrics and trauma surgery regarding the usage of REBOA in each respective field, and there have also been simulations regarding trauma in pregnancy [8][9][10][11][12][13]. Specifically, no reported simulation-based education for the use of REBOA in traumatically injured pregnant patients was identified in the literature review.…”
Section: Introductionmentioning
confidence: 99%